2020
DOI: 10.3390/ijms21041503
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Neurovascular Interaction in Retinal Disorders

Abstract: The tightly structured neural retina has a unique vascular network comprised of three interconnected plexuses in the inner retina (and choroid for outer retina), which provide oxygen and nutrients to neurons to maintain normal function. Clinical and experimental evidence suggests that neuronal metabolic needs control both normal retinal vascular development and pathological aberrant vascular growth. Particularly, photoreceptors, with the highest density of mitochondria in the body, regulate retinal vascular de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 247 publications
0
23
0
Order By: Relevance
“…The retina is the most energy-demanding tissue in the human body. A complex and organized retinal vascular network plays the critical role in delivering metabolites, which include oxygen, glucose, and lipid, to the eye [ 37 ]. Recently, a specific oxygen-binding protein is identified and named neuroglobin [ 38 , 39 ].…”
Section: Pathogenesis Of Ropmentioning
confidence: 99%
See 1 more Smart Citation
“…The retina is the most energy-demanding tissue in the human body. A complex and organized retinal vascular network plays the critical role in delivering metabolites, which include oxygen, glucose, and lipid, to the eye [ 37 ]. Recently, a specific oxygen-binding protein is identified and named neuroglobin [ 38 , 39 ].…”
Section: Pathogenesis Of Ropmentioning
confidence: 99%
“…It can be converted to pyruvate as an energy source for oxidative phosphorylation. Lipid is another mitochondrial fuel for photoreceptors via fatty acid β-oxidation [ 37 ]. This process takes place in the mitochondria and peroxisome in mammals.…”
Section: Pathogenesis Of Ropmentioning
confidence: 99%
“…Gene deletion studies revealed Sema 4D contributes to diabetes induced vascular permeability and targeted antibodies against Sema 4D were additive with anti-VEGF antibodies in effectively reducing diabetes induced vascular permeability in animal models (Wu et al, 2020). Semaphorins act in guidance of the developing nervous system and these studies reveal a role in vascular function in the retina and a potential role in diabetic retinopathy (Fu et al, 2020).…”
Section: Introductionmentioning
confidence: 97%
“…One such feature is the blood-retinal barrier (BRB), an analog of the blood-brain barrier (BBB) in the brain, which prevents the free access of blood, especially large molecular weight blood substances, to the delicate neural tissue. As part of the central nervous system (CNS), the retina forms a neurovascular unit (NVU) through the interaction of neurons, vascular cells, and glial cells (astrocytes and Müller) [ 1 ]. A retinal NVU is an anatomical structure to retain environmental homeostasis and a function unit to keep retinal cell function.…”
Section: Introductionmentioning
confidence: 99%